Gamification in Educational Process: Realization - Шаховська, Наталія; Рейман, Кшиштоф; Бобало, Юрій; Бригілевич, Володимир; Shakhovska, Nataliya; Rejman, Krzysztof; Bobalo, Yuriy; Brygilevych, Volodymyr (Видавництво Львівської політехніки, 2022)
У статті наведено архітектуру системи освіти з гейміфікацією. Система оцінювання практичних знань і умінь через гру покликана оптимізувати навчально-виховний процес та прояви творчого мислення студентів. Основна мета цієї системи – спрощення та автоматизація процесу навчання в закладах освіти.

The paper presents an architecture of the education system with gamification. The system for assessing practical knowledge and skills through play is designed to optimize the educational process and the manifestation of students’ creative thinking. The main purpose of this system is to simplify and automate the learning process in educational institutions.
Гейміфікація у освітньому процесі: реалізація
Keywords: gamification; educational process; web-site; class diagram